Contemporary and future research of digital humanities: a scientometric analysis - Wirapong Chansanam; Abdul Rahman Ahmad; Chunqiu Li (Institute of Advanced Engineering and Science, 2022)
This article analyses the special publications from 1999 to 2021, focusing on the scope and effect of digital humanities relevance research. The bibliometric analysis offers information on article publishing patterns, notable authors, cited references, institutions, nations, etc. Additionally, this paper covers the structure of knowledge of Digital humanities, including famous themes, co-citations, and bibliographic networks. Scopus database was used to obtain bibliographic data on September 25th, 2021, from papers published between 1999 and 2021. The bibliographic data for 1,249 publications using open-source analytic tools like the biblioshiny package in RStudio and the VOSviewer software shows it already. It employed the bibliometric package. These programmes visualized bibliography data based on their co-occurrence, co-citation, and coupling. The journal's publishing output and status in the area continue to rise, with 3,270 research papers indexed by Scopus to date. Additionally, the examination provides a thorough grasp of preceding patterns and forecasts a journal's future propensity.